Предмет: Математика,
автор: makssorokin902
Решите пожалуйста очень надо
Приложения:
Ответы
Автор ответа:
0
a) F(x)=x^6/6 -12x^2/2+x= x^6/6-6x^2+x +C
b)f(x)=-x^-4
F(x)=-x^(-4+1)/(-4+1) = -x^-3/-3 = x^-3/3 = 1/3x^3+C
b)f(x)=-x^-4
F(x)=-x^(-4+1)/(-4+1) = -x^-3/-3 = x^-3/3 = 1/3x^3+C
Автор ответа:
0
а) F(x) = x⁶/6 - 6x² + x + C
в) F(x) = -1/x³ : (-3) + C = 1/(3x³) + C
в) F(x) = -1/x³ : (-3) + C = 1/(3x³) + C
Похожие вопросы
Предмет: Информатика,
автор: polinasof
Предмет: Русский язык,
автор: AlexDela564
Предмет: Химия,
автор: timi4218
Предмет: Физика,
автор: mimisiляля